Spectacle, camera, authorship and surveillance in ‘found footage’ - Aguilar Alcalá, Sergio José (2020)
In this paper, the characteristics of films known as ‘found footage’ are discussed thorugh the ontology of cinematic camera, the distinction between fiction and non-fiction, between the shooting of a film and the film itself, and between an explicit author and an authorial agency of enunciation. In order to do this, the theories of Edward Branigan and Carl Plantinga will be essentil. Some films are analyzed with these axis, trying to understand the singular way each movie articulates the universal issue of the genre: the gap between the enunciated content and its enunciation. This irreductible gap, as psychoanalysis understands it, is necessary to understand the kind of truth we may find in ‘found footage’.